The evolution of primary sexual characters in animals - Leonard, Janet L. (Janet Louise), 1953-; Córdoba-Aguilar, Alex (Oxford University Press, 2010)
Primary sexual traits, those structures and processes directly involved in reproduction, are some of the most diverse, specialized, and bizarre in the animal kingdom. Moreover, reproductive traits are often species-specific, suggesting that they evolved very rapidly. This diversity, long the province of taxonomists, has recently attracted broader interest from evolutionary biologists, especially those interested in sexual selection and the evolution of reproductive strategies. Primary sexual characters were long assumed to be the product of natural selection, exclusively. A recent alternative.